The Manifesto Corpus: A new resource for research on political parties and quantitative text analysis - Nicolas Merz; Sven Regel; Jirka Lewandowski (Research & Politics, 2016)
This article presents a digital, open-access, multilingual, annotated corpus of electoral programs. It complements the recent methodological innovations in (semi-) computerized content analysis by providing a large, standardized text corpus for the political science community. The corpus is based on the collection of the Manifesto Project, which comprises of (at the time of writing) the largest hand-annotated text corpus of electoral programs available. Since 2009 the project's costly and time-intensive procedure of collecting and coding documents has been fully digitized. As a result, it now provides more than 1800 machine readable documents from 40 different countries. Six hundred of these documents contain content-analyzed annotations at the level of single (quasi-) sentences, which correspond to the Manifesto Project coding scheme. Additionally, the corpus will continually be extended by incorporating new elections and digitizing older documents. The database also provides meta-information for each document (eg. party, election, language, etc.) that allow it to be referenced back to the Manifesto Dataset. The corpus is stored in a standardized format in an online database, and an API and R package (manifestoR) guarantee easy access.
Keywords: 330; electoral programs; text corpus; R package